PENDIDIK DALAM PANDANGAN PENDIDIKAN ISLAM - Mardatillah , Azizah; Ramadhani, Najmi; Gusmaneli, Gusmaneli (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Educators play a big role in determining the value or results of education. In Islam, education is seen as an important and even central medium in forming Muslim individuals, which is in line with the goals of Islam itself. Because of this, Islam has a teaching mechanism that an educator must have, of course this teaching is also seen as a form of worship. Because the profession of teaching as an educator is worship, the process of educating requires a good and sincere attitude. Educators from an Islamic education perspective have certain criteria, at least having adequate knowledge capacity, being devout and having noble character.